Legal Protection of Workers in Higher Education Institutional Restructuring in Indonesia: Perspectives of Legal Certainty and Justice: Indonesian - Pradipta Prihantono; Heru Sugiyono; Andriyanto Adhi Nugroho (International Journal of Social Sciences and Humanities, 2026)
Institutional restructuring in higher education is strategies used to improve governmance quality, management effeicienty, competitiveness, and institutional sustainability. Such restructuring may take the form of mergers, institutional objectives, it may alaso raise legal issues, particulary concerning employment status, financial right, welfare guarantees and legal certainty for academic and non=academic staff. This articlr aims to analyse the legal protection of workers in higher education instutional restructuring in Indonesia and to formulate legal protection model based on legal certainty an justice. This study uses a normative juridical method with statutory anc conceptual approaches. The findings show that labor law and higher education law provide general protection for workers; homewer, the do not specifically regulate employmen transition mechanisms in higher education restructuring, as aresult employe protection often depend on the internal policies of each governing body. Therefore stronger techinal regulations are needed to govern employment tranfer, recognition of service periode, financial right, employee participation and dispute resolution in higher education institutional restructuring.